Functional outcome of Metacarpal Fracture managed with Miniplate and Screws - Shah, Gyanendra; KC, Bachchu Ram; chand, Pankaj; Sah, Deb Narayan (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Early techniques of splint immobilization work well for simple metacarpal fractures. However, if significantly shorting, rotational deformity, and angulations occur, surgical treatment is required. The aim of this article was to study the functional outcome of metacarpal fractures treated by open reduction and internal fixation with mini plates and screw in low resource condition of Nepal.Material and Methods: This retrospective study was done over a period of one year 2012 to 2013 in Bir Hospital, Patan hospital and Shree Birendra hospital. The functional outcome after treatment was assessed by ability to perform acts of daily life and calculating American Society for Surgery of the Hand Total Active Flexion (ASSH-TAF).Results: Out of 30 patients twenty three were male (76.7%) and seven were female (23.3%). Among them, 7 patients (23.3%) showed union in 6 weeks. 18 Patients (60%)  had union in 4 weeks. 3 patients (10%) had at five weeks and 2 patients had union at 6 weeks. We observed ASSH-TAF score at 2 weeks, 1month, 3 months, and 6 months. Results showed 24 patients (80%) had excellent, 4(13.3%) had good and 2(6.7%) had poor result.Conclusion: The use of miniplate and screws is a reasonable option for treating in displaced metacarpal fracture as it provides a rigid, Secure an anatomical stable reduction, which is sufficient to allow early mobilization of the adjacent joints, hence the mini plate fixation is effective means of immobilization of fracture of metacarpal with less complication and excellent functional outcome.